Growth Hormone Therapy for Small for Gestational Age Short Stature Develops Type 2 Diabetes - Naohiro Nomura; Yuko Tanabe; Miki Minami; Junji Takaya; Kazunari Kaneko (Case Reports in Pediatrics)
Growth Hormone therapy has been shown to induce transient insulin resistance in children, and there is concern regarding the diabetogenic potential of GH therapy in children born small for gestational age (SGA). In this case, female patient born SGA with a weight of 2,750 g (−1.73 standard deviation (SD)) and length of 45.5 cm (−2.6 SD). The patient’s father and paternal grandfather were diagnosed with type 2 diabetes mellitus. At 3 years of age, the patient presented with short stature; height and weight were 85 cm (−2.5 SD) and 13 kg (−0.19 SD), respectively. She was placed on GH therapy. At 11 years of age, her fasting blood glucose and hemoglobin A1c levels were 116 mg/dL and 7.4%, respectively. Blood test results were negative for anti-glutamic acid decarboxylase and anti-islet antigen-2 antibodies. The patient discontinued GH therapy and started diet therapy and oral metformin (500 mg/day) administration. Five months later, the hemoglobin A1c level was 5.3% and glycemic control further improved. To our knowledge, family history may be an important risk factor for GH-induced diabetes. So, the GH dosage for patients born SGA with family history of diabetes should be adjusted so as not to be too excessive, and long-term follow-up studies will be required to evaluate fully the effects of GH therapy for them.